Influence of different training programmes on basic coordination of female handball players - Bojic, I.; Petkovic, D.; Kocic, M. (Acta Kinesiologica, 2010)
The aim of this research is determining the influence of different training programmes (the ones without the ball and the ones in which in ball is used at the beginning and the end of a training session) on basic coordination of female handball players. 60 girls, aged 12 to 14 (± 6 months) took part in the research. They were divided into two subgroups; the experimental E1 group (30 players) and E2 group (30 players). All of the girls were training handball for at least a year. A battery of seven tests was used for evaluating basic coordination. Qualitative differences, as well as the hierarchy of variables which add to a better discrimination between the initial and the final testing of both experimental groups but also enable differentiation between the groups in the final testing, were determined by the canonical discriminating analysis. The results showed that both experimental programmes had a positive influence on the changes of basic coordination of the handball players. However, the programme of the E2 subgroup (in which the ball was used in all the training phases) brought about the changes in a larger number of variables than the E1 programme (which included exercises and movements without the ball).